ANALISIS ECM PDB, KURS DAN JUMLAH UANG BEREDAR TERHADAP INFLASI - Budiman, Putra Arif (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa), 2021)
The turnaround of monetary power can be seen as a problem that requires attention in Indonesia and the world. Inflation as one of the segments that influence improvement has a significant role if at the right level it is necessary to drive financial progress in a positive way. Swelling can otherwise affect the economy. The stability of gross domestic product, currency exchange rates, and the amount of money in circulation are some of the important variables that influence inflation movements. This study aims to show the relationship of gross domestic product, the amount of money in circulation, the exchange rate, and the price of gold to inflation by using the Error Correction Model  (ECM). The results showed based on the results of calculations with a model of correction of errors using both rupiah and gold dinar exchange rates, it can be known that in the short term, the rupiah exchange rate, income has a significant effect on inflation. In the long run, exchange rates have an important influence